2019
DOI: 10.1073/pnas.1906571116
|View full text |Cite
|
Sign up to set email alerts
|

Optimal compressed sensing strategies for an array of nonlinear olfactory receptor neurons with and without spontaneous activity

Abstract: There are numerous different odorant molecules in nature but only a relatively small number of olfactory receptor neurons (ORNs) in brains. This “compressed sensing” challenge is compounded by the constraint that ORNs are nonlinear sensors with a finite dynamic range. Here, we investigate possible optimal olfactory coding strategies by maximizing mutual information between odor mixtures and ORNs’ responses with respect to the bipartite odor-receptor interaction network (ORIN) characterized by sensitivities bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 92 publications
1
30
0
Order By: Relevance
“…Some authors have proposed that the random projections to cortex are a mechanism for creating sparse, high dimensional representations suitable for downstream linear classification [21, 39, 65], or are evidence for compressive sensing in olfaction [18, 25]. Others have suggested that compressive sensing occurs at the receptors [19, 27], and that the random projections reformat the compressed data for downstream decoding [27]. We propose a complementary view: random projections combine with strong gating to leverage information in silent receptors, enabling network decoding of responses from a small number of receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have proposed that the random projections to cortex are a mechanism for creating sparse, high dimensional representations suitable for downstream linear classification [21, 39, 65], or are evidence for compressive sensing in olfaction [18, 25]. Others have suggested that compressive sensing occurs at the receptors [19, 27], and that the random projections reformat the compressed data for downstream decoding [27]. We propose a complementary view: random projections combine with strong gating to leverage information in silent receptors, enabling network decoding of responses from a small number of receptors.…”
Section: Resultsmentioning
confidence: 99%
“…There are perhaps 10 4 or more monomolecular odorants [1][2][3], far more than the number of receptor types in animals (⇠ 50 in fly, ⇠ 300 in human, ⇠ 1000 in rat, mouse and dog [4][5][6][7]). The problem of representing high-dimensional chemical space in a low-dimensional response space may be solved by the presence of many receptors that bind to numerous odorants [8][9][10][11][12][13][14], leading to a distributed, compressed, and combinatorial representation [12,[15][16][17][18][19][20][21] processed by activity in networks of neurons [22,23]. Some mechanisms for such distributed representation propose that each odorant activates specific subsets of neurons [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Plotting the mutants versus normalized TAL and AHP shows 17 colonies with extreme activity and, generally, that mutants efficient at producing one product are inefficient at 18 producing the other (Figure 4A). To validate these results, we re-transform and test several mutants in bulk, 19 finding good agreement (Figures 4B, Figure S13, Table S3). Interestingly, the TLLL mutant based on 20 consensus design 18 of TAL enriched members from the UMAP also shows high TAL production, though it 21 retains higher AHP side-activity than the TLLN mutant 122 (Figure S14).…”
mentioning
confidence: 78%
“…Metabolic biosensing allows inference of product formation even without direct product detection because the enzyme’s activity perturbs the host cell’s metabolite profile. Provided such perturbations are distinct for each activity, all activities generated by a mutant library can be detected, similar to the “compressed sensing” of smell sensation 19 . Such indirect sensing has beneficial features for enzyme engineering.…”
Section: Discussionmentioning
confidence: 99%